Cirrhosis and Rapid Virological Response to Peginterferon Plus Ribavirin Determine Treatment Outcome in HCV-1 IL28B rs12979860 CC Patients. (9th July 2013) - Aghemo, Alessio; Degasperi, Elisabetta; Rumi, Maria Grazia; Galmozzi, Enrico; Valenti, Luca; De Francesco, Raffaele; De Nicola, Stella; Cheroni, Cristina; Grassi, Eleonora; Colombo, Massimo
Abstract : Background . The rs12979860 CC genotype of the interleukin 28B (IL28B) polymorphism is associated with high rates of sustained virological response (SVR) to peginterferon (PegIFN) and ribavirin (Rbv) in hepatitis C virus genotype-1 (HCV-1) patients. The impact of baseline predictors of treatment outcome and their interplay with viral kinetics in HCV-1 CC patients has not been fully evaluated. Aim . To identify baseline and on-therapy predictors of treatment failure in HCV-1 IL28B CC patients. Methods . Treatment-naïve HCV-1 patients, compliant to PegIFN and Rbv who did not discontinue treatment for nonvirological reasons, were analyzed. Results . 109 HCV-1 IL28B CC were studied. Sixty were males, 39 with BMI >25, 69 with >600, 000 IU/mL HCV RNA, 15 with HCV1a, and 30 with cirrhosis. Overall, 75 (69%) achieved an SVR; cirrhosis was the only baseline predictor of treatment failure (OR: 2.58, 95% CI: 1.07–6.21) as SVR rates were 53% in cirrhotics versus 75% in noncirrhotics (P = 0.03 ). HCV RNA undetectability (<50 IU/mL) at week 4 (RVR) was achieved by 58 patients (53%). The SVR rates were independent of RVR in noncirrhotics, 76% (34/45) RVR (+) and 74% (25/34) RVR (−) (P = 0.9 ). In cirrhotic patients, SVR rates were significantly higher in RVR (+) compared to RVR (−) (10/13 (77%) versus 6/17 (35%) P = 0.03 ). Conclusions . In HCV-1 IL28B CC patients, cirrhosis is the only clinical baseline predictor of PegIFN and Rbv treatment failure. However, in IL28B CC cirrhotics, the achievement of RVR identifies those patients who still have high rates of SVR to Peg-IFN/Rbv therapy.